Pengaruh Brand Ambassador terhadap Keputusan Pembelian pada Produk Luwak White Koffie di Surabaya dengan Citra Merek sebagai Variabel Intervening - Haque, Muhammad Hirzal; Dermawan, Rizky Dermawan; Amriel, Egan Evanzha Yudha (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of brand ambassadors on purchasing decisions on civet white coffee in Surabaya with brand image as an intervening variable. The research method used is a quantitative research method with a sampling technique using non-probability sampling and purposive sampling techniques. The population and sample in this study were people in the city of East Surabaya who had bought and consumed civet white coffee products with a total of 99 respondents. This study uses the Smart-PLS test tool. The results of the study show that: 1) Brand Ambassadors had an effect on Purchasing Decisions, 2) Brand Ambassadors had an effect on Brand Image, 3) Brand Image had an effect on Purchasing Decisions and 4) Brand Ambassadors through Brand Image had an effect on Purchasing Decisions. Keywords: Brand Ambassador; Brand Image; Luwak White Koffie